2017
DOI: 10.3389/fnins.2017.00004
|View full text |Cite
|
Sign up to set email alerts
|

Semi-automatic 10/20 Identification Method for MRI-Free Probe Placement in Transcranial Brain Mapping Techniques

Abstract: The International 10/20 system is an important head-surface-based positioning system for transcranial brain mapping techniques, e.g., fNIRS and TMS. As guidance for probe placement, the 10/20 system permits both proper ROI coverage and spatial consistency among multiple subjects and experiments in a MRI-free context. However, the traditional manual approach to the identification of 10/20 landmarks faces problems in reliability and time cost. In this study, we propose a semi-automatic method to address these pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…When structural magnetic resonance imaging is not used, a MRI-free method, the international 10–20 system is adopted ( Jasper, 1958 ; Herwig et al, 2003 ). Previous findings have demonstrated that each 10–20 landmark on the scalp corresponds to a specific cortical structure and that there is a consistent correlation between scalp positions and underlying cerebral structures across subjects ( Myslobodsky et al, 1990 ; Okamoto et al, 2004 ; Xiao et al, 2017 ). Thus, according to the 10–20 system, attaining the approximate large-scale anatomical positions in which we are interested is achievable.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…When structural magnetic resonance imaging is not used, a MRI-free method, the international 10–20 system is adopted ( Jasper, 1958 ; Herwig et al, 2003 ). Previous findings have demonstrated that each 10–20 landmark on the scalp corresponds to a specific cortical structure and that there is a consistent correlation between scalp positions and underlying cerebral structures across subjects ( Myslobodsky et al, 1990 ; Okamoto et al, 2004 ; Xiao et al, 2017 ). Thus, according to the 10–20 system, attaining the approximate large-scale anatomical positions in which we are interested is achievable.…”
Section: Discussionmentioning
confidence: 97%
“…Considering the limited spatial coverage and spatial resolution, as well as the limited deep imaging capacity ( Vanderwert and Nelson, 2014 ; Xiao et al, 2017 ), it is fundamental and indispensable to investigate the feasibility of fNIRS to detect the MNS. However, few studies have examined the feasibility.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the system configuration, the conventional 10–20 positioning systems is simple and inexpensive, but an unreliable electrode positioning can occur from the manual identification of the anatomical landmarks [ 7 , 8 , 13 15 ]. To address this issue, an extra device such as a vision-based position tracker, a commercial ultrasonic digitizer or a magnetic digitizer has been used so far [ 4 , 6 , 9 ]. Compared to those system, only an RGB-D camera is necessary in the proposed system.…”
Section: Discussionmentioning
confidence: 99%
“…Tsuzuki et al [ 5 ] proposed the MinR 10–20 system that used landmarks of nasion, right and left preauricular points and posterior point on the occipital protuberance. Xiao et al [ 6 ] proposed a semi-automatic 10–20 identification method using the virtual 10–20 landmark determination in the computational space of reconstructed head surface. The virtual landmarks were identified using a visually guided navigation system, which used a magnetic digitizer.…”
Section: Introductionmentioning
confidence: 99%
“…The Imagent manual (2005) provides the details of fNIRS as applied to the assessment of human brain. The fNIRS headcap was fastened to the subject’s head with Velcro straps, using the 10-20 International convention (Xiao et al, 2017) (Figure 2 A.). In total, 4 detectors and 24 channels were employed.…”
Section: Methodsmentioning
confidence: 99%